The Impact of Urbanization Rate, Per Capita Income, and Carbon Emissions on Renewable Energy Consumption in ASEAN-5 Countries - Setyame, Rike Vidyana; Nikensari, Sri Indah; Iranto, Dicky (TOFEDU: The Future of Education Journal, 2025)
The phenomenon of climate change, increasing high temperatures, and significant global warming encourages many countries, including the ASEAN-5 Region to make an energy transition through the use of renewable energy and become a solution that can reduce the negative impacts of both economic, social, and environmental from the energy system to sustainability. However, in its implementation, renewable energy is still a challenge, especially economic and social factors for every country in the world, especially in ASEAN-5. This study aims to analyze the effect of urbanization levels, per capita income, and carbon emissions on renewable energy consumption in ASEAN-5 countries (Indonesia, Malaysia, Thailand, Vietnam, and the Philippines) during the period 2015–2023. Using quantitative methods with data sourced from Our World in Data and the World Bank, analyzed using the panel data regression method with the Fixed Effect Model (FEM) approach. The results of the study show that the level of urbanization has a positive relationship and has a significant effect on renewable energy consumption, then per capita income has a positive relationship but does not have a significant effect on renewable energy consumption, and carbon emissions have a negative relationship and have a significant effect on renewable energy consumption. Furthermore, independent variables simultaneously influence renewable energy consumption in ASEAN-5 countries from 2015 to 2023. These findings provide policy implications for governments in realizing the Paris Agreement and sustainable development.